Prealgebra (7th Edition)

Published by Pearson
ISBN 10: 0321955048
ISBN 13: 978-0-32195-504-3

Chapter 3 - Section 3.3 - Solving Linear Equations in One Variable - Exercise Set: 39

Answer

The solution is -6

Work Step by Step

6( 7x - 1) = 43x Apply the distributive property 6$\times$7x - 6$\times$1 = 43x Multiply 42x -6 =43x Subtract 43x from both sides 42x -6 -43x=43x -43x -x - 6 =0 Add 6 to both sides -x - 6 + 6 = 0 +6 -x = 6 Divide by -1 on both sides $\frac{-x}{-1}$ = $\frac{6}{-1}$ x = -6 The solution is -6 Check 6( 7x - 1) = 43x 6[7(-6)- 1) = 43(-6) 6[-42 -1 ]=-258 6[-43]=-258 -258=-258
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.